Efecto de “plectranthus amboinicus” en los parámetros de la canal y visceral de pollos cobb 500 - Leon Armijos, Erika Maria (Machala : Universidad Técnica de Machala, 2022)
he present experimental work was carried out in the experimental farm "Santa Inés" in the Faculty of Agricultural Sciences of the Technical University of Machala, in the province of El Oro, Ecuador. With the objective of evaluating the effect of the inclusion of the ground dehydrated Plectranthus amboinicus on the parameters of the carcass and at the visceral level of the Cobb 500 chickens. For which 240 Cobb 500 mixed chicks of 1 day of age were used, in a design completely random (DCA), following the rules established in the general guide of Voluntary Character, on the Adoption and certification of Good Poultry Practices, providing the birds with adequate food, hydration, temperature and humidity. Managing a basic vaccination schedule appropriate to the area, consisting of vaccines; Gumboro “Cepa Intermedia” and New Castle “Cepa La Sota”, with their respective reinforcements. The food was formulated in an artisanal way, using raw materials from the “Balmar” company. 6 treatments and 4 replications with 10 chicks were implemented in each experimental unit. The first treatment (T1 or control) incorporates antibiotics as growth promoter and coccidiostat in the chicken balance, the second treatment (T2) adds 0.25% of dehydrated P. amboinicus to replace the APC, the third treatment (T3) 0.50% of P. amboinicus is added, the fourth treatment (T4); 0.75%, the fifth treatment (T5); 1% of the dehydrated, and the sixth treatment (T6) presents 0.1% of the ground dehydrated stems of P. amboinicus. The variables studied were the following: Antemortem weight (g), Bleeding weight (g), Plucking weight (g), Gutted weight (g), Carcass yield (%), Breast weight (g), Thigh weight ( g), Thigh weight (g), Shoulder weight (g), Head weight (g), Neck weight (g), Leg weight (g), Wing weight (g), Heart weight (g), Spleen weight (g) , Liver weight (g), Gizzard weight (g), Intestines weight (g), Gizzard fat weight (g) and Abdominal fat thickness (cm). Data collected on day 35 of rearing, time in which the experiment is concluded with the sacrifice of 48 birds, 2 chickens from each replica (8 per treatment). The data collected was analyzed with the statistical program Statgraphics Centurión XV.I.®, using Anova of one factor, after establishing the assumption of Normality and Homogeneity, for the data that were not adjusted, the Kruskal-Wallis test was used, establishing the differences. To establish the differences and confidence intervals, Fisher's least significant difference (LSD) procedure was used with a 95.0% confidence level. The results obtained indicate a positive effect on the carcass and at the visceral level, when compared with the control. The inclusion of 1% oreganon presented better weights antemortem, shattering, plucking, carcass, thighs, thighs and breast. But when analyzing them in percentages, with respect to antemortem weight, it is observed that the inclusion of leaves and stem of oreganon gives good results at the carcass and visceral level, when compared with antibiotic and coccidiostatic feeding in broilers. Providing us with a natural, low-cost and effective alternative to the implementation of antibiotics such as APC.
El presente trabajo de experimentación se llevó a cabo en la granja experimental “Santa Inés” en la Facultad de Ciencias Agropecuarias de la Universidad Técnica de Machala, en la provincia de El Oro, Ecuador. Con el objetivo de evaluar el efecto de la inclusión del deshidratado molido de Plectranthus amboinicus sobre los parámetros de la canal y a nivel visceral de los pollos Cobb 500. Para lo cual se empleó 240 pollitos mixtos Cobb 500 de 1 día de edad, en un diseño completamente al azar (DCA), siguiendo las normas establecidas en la guía general de Carácter Voluntario, sobre la Adopción y certificación de Buenas Prácticas Avícolas, proporcionando a las aves una adecuada alimentación, hidratación, temperatura y humedad. Manejando un calendario básico vacunal adecuado a la zona, consistente en las vacunas; Gumboro “Cepa Intermedia” y New Castle “Cepa La Sota”, con sus refuerzos respectivos. La alimentación se formuló de forma artesanal, utilizando materias primas procedentes de la empresa “Balmar”. Se implementaron 6 tratamientos y 4 réplicas con 10 pollitos en cada unidad experimental. El primer tratamiento (T1 o testigo) incorpora antibiótico como promotor de crecimiento y coccidiostático en el balanceado de los pollos, al segundo tratamiento (T2) se le añade 0,25% de deshidratado de P. amboinicus en reemplazo del APC, el tercer tratamiento (T3) se añade 0,50% de P. amboinicus, el cuarto tratamiento (T4); 0,75%, el quinto tratamiento (T5); 1% del deshidratado, y el sexto tratamiento (T6) presenta 0,1% del deshidratado molido de tallos de P. amboinicus. Las variables estudiadas fueron las siguientes: Peso antemortem (g), Peso al desangre (g), Peso al desplume (g), Peso eviscerado (g), Rendimiento de la canal (%), Peso pechuga (g), Peso muslos (g), Peso contramuslos (g), Peso espaldilla (g), Peso cabeza (g), Peso cuello (g), Peso patas (g), Peso alas (g), Peso corazón (g), Peso bazo (g), Peso hígado(g), Peso molleja (g), Pesos intestinos (g), Peso grasa de la molleja (g) y Espesor de grasa abdominal (cm). Datos recogidos al día 35 de crianza, tiempo en el que se concluye el experimento con el sacrificio de 48 aves, 2 pollos de cada réplica (8 por tratamiento). Los datos recogidos se analizaron con el programa estadístico Statgraphics Centurión XV.I.®, utilizando Anova de un factor, luego de establecer el supuesto de Normalidad y Homogeneidad, para los datos que no se ajustaron, se utilizó La prueba de Kruskal- Wallis, estableciendo las diferencias. Para establecer las diferencias e intervalos de confianza, se utilizó el procedimiento de la diferencia mínima significativa (LSD) de Fisher con un nivel del 95.0% de confianza. Los resultados obtenidos, indican un efecto positivo sobre la canal y a nivel visceral, al comparar con el testigo. La inclusión del 1% de oreganon presentó mejores pesos antemortem, al desgrangre, al desplume, de la canal, muslos, contramuslos y pechuga. Pero al analizarlos en porcentajes, respecto al peso antemortem, se observa que la inclusión de hojas y tallo de oreganon da buenos resultados a nivel de la canal y visceral, al compararlo con la alimentación con antibiótico y coccidiostático en pollos de engorde. Proporcionándonos una alternativa natural, de bajo costo y efectiva a la implementación de antibióticos como APC.
Keywords: RENDIMIENTO DE LA CANAL; DESPIECE; VÍSCERAS